Preparation method of highly dispersible polytetrafluoroethylene powder and dry electrode sheet

By performing PEGDME coating and plasma treatment on the surface of the polytetrafluoroethylene powder, the problem of poor dispersion of PTFE powder in the dry electrode is solved, and more uniform dispersion and higher electrochemical properties are achieved.

CN119019715BActive Publication Date: 2025-02-18SHENZHEN QINGYAN ELECTRONIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411509826.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

In the dry electrode process, the dispersion of polytetrafluoroethylene (PTFE) powder is poor, resulting in uneven distribution in the electrode, affecting the mechanical strength, conductivity and electrochemical reaction rate of the electrode.

Method used

By coating the polytetrafluoroethylene powder with polyethylene glycol dimethyl ether (PEGDME) and undergoing plasma treatment, the surface performance of PTFE is improved and its compatibility and adhesion with other powder materials are enhanced, thereby Improve its dispersibility.

Benefits of technology

The modified PTFE can be better dispersed in the electrode, forming a uniform bonding network structure, improving the conductivity, mechanical strength and structural stability of the electrode, and enhancing the rate performance and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119019715B_ABST
    Figure CN119019715B_ABST
Patent Text Reader

Abstract

The embodiment of the present invention discloses a method for preparing a highly dispersible polytetrafluoroethylene powder and a dry electrode plate, the method comprising: step 1: impregnating the polytetrafluoroethylene powder with a polyethylene glycol dimethyl ether solution, removing the residue on the surface of the polytetrafluoroethylene powder after the impregnation, and drying; step 2: plasma treating the coated polytetrafluoroethylene powder to obtain a plasma-treated polytetrafluoroethylene powder; step 3: washing the plasma-treated polytetrafluoroethylene powder, and then drying to obtain a highly dispersible polytetrafluoroethylene powder. The present invention reduces the hydrophobicity of the PTFE surface, improves its compatibility with other powders, and thus improves the dispersion effect; controls the particle size, morphology and molecular weight of PTFE, optimizes its dispersion behavior, and avoids particle agglomeration; improves the powder dispersibility of PTFE by surface modification, increases electrolyte wettability, and improves electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dry electrode production, and in particular to a preparation method of highly dispersible polytetrafluoroethylene powder and a dry electrode pole piece. Background Art

[0002] As the global demand for renewable energy increases, lithium-ion batteries have been widely used as an efficient energy storage device. From consumer electronics to electric vehicles and large-scale energy storage systems, the market demand for lithium-ion batteries continues to grow. Although the traditional wet electrode manufacturing process is mature, it has many limitations, such as environmental pollution, high production costs and process complexity. In order to overcome these problems, dry electrode technology came into being and became an important innovation direction in the field of lithium-ion battery manufacturing.

[0003] The dry electrode process is a solvent-free electrode preparation technology. Compared with the traditional wet electrode process, the dry electrode process does not require the use of organic solvents. The electrode material and the binder are evenly mixed, pressed into a film, and finally the electrode is prepared by physical means. This process has broad application prospects in lithium-ion batteries, capacitors and other fields.

[0004] Dry electrode technology uses PTFE (Polytetrafluoroethylene) powder as a binder. Although PTFE has excellent chemical stability and mechanical properties as a binder in dry electrodes, PTFE is a polymer material with extremely low surface energy (surface tension is about 18-20 mN / m), and its surface has strong hydrophobicity and liquid repellency. This surface property makes it easy for PTFE powder particles to attract and accumulate each other, and it is not easy to form a uniform dispersion with other powder particles. The high surface energy leads to an increase in the van der Waals force between particles, which makes the particles tend to spontaneously aggregate during the mixing process, thereby forming agglomerates.

[0005] In the dry electrode process, PTFE usually plays the role of connecting active materials, conductive agents and other components together to form a stable electrode structure. PTFE powder agglomerates, resulting in uneven distribution in the electrode, which makes it impossible to form a uniform fiber network structure, thereby affecting the mechanical strength and flexibility of the electrode. The agglomerated PTFE area has strong mechanical properties due to the local excess of PTFE, while other areas may show poor strength and brittleness due to insufficient PTFE. Ultimately, the electrode sheet may crack or break during the subsequent rolling process, reducing the consistency and stability of the electrode sheet.

[0006] Agglomerated PTFE particles will form local high-resistance areas, resulting in obstruction of the conduction paths of electrons and ions in the electrode, thereby increasing the overall resistance of the electrode and reducing the conductivity of the electrode sheet. Agglomerated PTFE particles will form an insulating layer in the electrode sheet, affecting the current distribution inside the electrode, increasing the collective resistance (IR) of the electrode, increasing the ohmic polarization during the charge and discharge process, and reducing the rate performance and energy density of the battery.

[0007] PTFE agglomeration causes the overall uniformity of the electrode sheet to deteriorate, which directly affects the electrochemical reaction rate of the battery. On the one hand, the agglomerates affect the effective contact area and contact resistance of the active material, reducing the number of active sites on the electrode; on the other hand, the locally enriched PTFE may make it difficult for the electrolyte to penetrate evenly, increasing the resistance to ion conduction.

[0008] Due to its high surface energy and strong hydrophobicity, PTFE powder is prone to agglomeration when mixed with other powders (such as conductive agents and active materials), resulting in poor dispersion in the mixture and affecting the uniformity of the electrode sheet. Therefore, it is necessary to improve the dispersion of PTFE powder. Summary of the invention

[0009] The technical problem to be solved by the embodiments of the present invention is to provide a method for preparing highly dispersible polytetrafluoroethylene powder and a dry electrode plate to improve the dispersibility of the polytetrafluoroethylene powder.

[0010] In order to solve the above technical problems, the present invention provides a method for preparing highly dispersible polytetrafluoroethylene powder, comprising:

[0011] Step 1: impregnating polytetrafluoroethylene powder with a polyethylene glycol dimethyl ether solution, taking out the polytetrafluoroethylene powder after the impregnation is completed, removing the residue on the surface of the polytetrafluoroethylene powder and drying it to obtain a coated polytetrafluoroethylene powder;

[0012] Step 2: Plasma-treating the coated polytetrafluoroethylene powder to obtain plasma-treated polytetrafluoroethylene powder;

[0013] Step 3: Wash the plasma-treated polytetrafluoroethylene powder, and then dry it to obtain highly dispersed polytetrafluoroethylene powder.

[0014] Furthermore, the particle size of the polytetrafluoroethylene powder impregnated with the polyethylene glycol dimethyl ether solution is 1 to 20 microns.

[0015] Furthermore, the polyethylene glycol dimethyl ether solution is a polyethylene glycol dimethyl ether solution containing a solvent or a polyethylene glycol dimethyl ether solution without a solvent.

[0016] Furthermore, the concentration range of the polyethylene glycol dimethyl ether solution is 5% to 100%.

[0017] Furthermore, in step 1, the immersion temperature is 20°C to 150°C, the immersion time is 1 to 24 hours, and the drying temperature is 10°C to 150°C.

[0018] Furthermore, ultrasonic treatment is used during the impregnation process to accelerate the penetration of the polyethylene glycol dimethyl ether solution into the surface of the polytetrafluoroethylene particles.

[0019] Furthermore, in step 2, the plasma treatment time is 0.5 minutes to 120 minutes.

[0020] Furthermore, in step 2, the plasma gas for the plasma treatment is one or more of argon, oxygen, nitrogen and ammonia, and the plasma gas flow rate is 10 to 50 sccm.

[0021] Furthermore, the drying temperature is 50° C. to 80° C., and the drying time is 1 to 2 hours.

[0022] Correspondingly, an embodiment of the present invention further provides a dry electrode plate, comprising highly dispersible polytetrafluoroethylene powder prepared by the method for preparing highly dispersible polytetrafluoroethylene powder as described above.

[0023] The beneficial effects of the present invention are as follows: the present invention adopts the method of coating the surface of polytetrafluoroethylene (PTFE) powder with polyethylene glycol dimethyl ether (PEGDME) and then adopts a plasma treatment method to perform surface modification, which can effectively improve the surface properties of PTFE and thus enhance its application effect in the dry electrode process. This modification strategy can effectively solve the problems of poor dispersibility of PTFE powder, insufficient adhesion ability and poor compatibility with other powder materials.

[0024] The present invention uses plasma treatment to introduce polar functional groups (such as hydroxyl groups, carboxyl groups, etc.) on the surface of PTFE coated with PEGDME, so that the wettability and hydrophilicity of the PTFE surface are significantly improved, thereby enhancing the compatibility and adhesion of PTFE with other materials (such as active materials and conductive agents) during the preparation of dry electrodes. The active groups formed on the surface of the PTFE coated with PEGDME under plasma treatment can form hydrogen bonds or van der Waals forces with other powders, which helps to improve mixing uniformity and reduce particle agglomeration.

[0025] The present invention has a stronger interface bonding force between PTFE coated with PEGDME and treated with plasma and a conductive agent (such as carbon black, carbon nanotubes), which helps to form a low-impedance electronic conduction channel and improve the conductivity of the electrode sheet. The surface-modified PTFE can better disperse and coat the active material particles in the electrode sheet, which helps the penetration of the electrolyte and the conduction of ions, thereby reducing the ohmic impedance and polarization phenomenon of the electrode sheet and improving the rate performance and energy density of the battery.

[0026] The modified PTFE of the present invention can form a uniform bonding network structure inside the electrode sheet, avoiding local expansion or contraction of the electrode sheet during the charge and discharge process, and improving the structural stability of the electrode sheet. The uniformly distributed PTFE can reduce the shedding of active materials and the stratification of the electrode sheet during the cycle process, thereby improving the cycle life and long-term performance of the electrode.

[0027] The molecular structure of PEGDME is terminated with methyl groups (-CH3) at both ends. The presence of methyl end groups makes PEGDME more stable and less susceptible to oxidation, degradation and cross-linking reactions. Therefore, it exhibits better durability and chemical stability during long-term use of the electrode sheet.

[0028] During the plasma treatment process of the present invention, the lower chemical reactivity of PEGDME can form a more uniform and stable modified layer on the PTFE surface, and PEGDME has higher heat resistance and environmental stability. During the battery preparation process, the PTFE coated with PEGDME is not easy to decompose or degrade during high temperature treatment or subsequent heat treatment, and the integrity of the surface modified layer can be maintained. In high temperature, high humidity or strong oxidizing environment, the PTFE coated with PEGDME exhibits stronger chemical corrosion resistance and environmental stability, and is not prone to hydrolysis or cross-linking reactions, thereby improving the long-term stability of the electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic flow chart of a method for preparing highly dispersible polytetrafluoroethylene powder according to an embodiment of the present invention.

[0030] Figure 2 It is a schematic diagram of cutting a 50 mm×50 mm film according to each embodiment of the present invention and testing the resistivity of five positions using a four-probe method. DETAILED DESCRIPTION

[0031] It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments may be combined with each other. The present invention is further described in detail below in conjunction with the drawings and specific embodiments.

[0032] In the embodiments of the present invention, if there are directional indications (such as up, down, left, right, front, back, etc.), they are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0033] In addition, in the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features.

[0034] Please refer to Figure 1 The method for preparing highly dispersible polytetrafluoroethylene powder according to an embodiment of the present invention comprises steps 1 to 3.

[0035] Step 1: impregnate polytetrafluoroethylene powder with polyethylene glycol dimethyl ether solution. After the impregnation is completed, take out the polytetrafluoroethylene powder, remove the residue on the surface of the polytetrafluoroethylene powder and dry it to obtain the coated polytetrafluoroethylene powder.

[0036] Material selection:

[0037] Polytetrafluoroethylene powder (PTFE): dry powder with a particle size of 1 to 20 microns.

[0038] Polyethylene glycol dimethyl ether (PEGDME): PEGDME with different molecular weights (400-100000) was selected to study its effect on the surface modification of PTFE.

[0039] Solvent: From an environmental protection perspective, deionized water, ethanol, isopropanol and other solvents are preferred.

[0040] Preparation of PEGDME solution:

[0041] According to the target concentration (5% to 100%), add PEGDME to the solvent and stir until it is completely dissolved. During the dissolution, stir on a magnetic stirrer (speed 300 rpm) and stir at a temperature of 30℃ to 50℃ for 30 minutes to ensure that the solution is uniform and transparent.

[0042] Coating and drying:

[0043] Place PTFE powder in PEGDME solution at 20℃~150℃ and 1~24 hours. Ultrasonic treatment (frequency 20~40 kHz) can be used to accelerate the penetration of PEGDME solution into the surface of PTFE particles during the immersion process. After immersion, take out the PTFE powder, drain the excess solution, and use filter paper to absorb the residual solvent on the surface.

[0044] Place the coated PTFE powder in a drying oven and dry it at a temperature (10℃~150℃). For water-soluble PEGDME solution, choose 50℃~80℃ for drying; for solvent-free PEGDME coating, choose 80℃~100℃ for drying to improve adhesion.

[0045] The drying time can be set to 1 to 3 hours. Intermittent turning is used during the drying process to ensure that the PTFE powder is dried evenly. After drying, samples are taken to observe the coating on the surface of the PTFE powder to ensure that PEGDME can be evenly covered on the surface of the PTFE particles without obvious agglomeration and residual solvent.

[0046] Step 2: Plasma-treating the coated polytetrafluoroethylene powder to obtain plasma-treated polytetrafluoroethylene powder.

[0047] Plasma treatment equipment:

[0048] Use low-pressure plasma treatment equipment or atmospheric pressure plasma treatment equipment, and select appropriate equipment according to the processing volume of PTFE powder and equipment characteristics. The equipment should include vacuum pump, plasma generator (RF, DC, microwave, etc.), gas flow control system, etc.

[0049] Plasma treatment process parameter settings:

[0050] Plasma treatment power: Select 10W to 1500W, optimized according to the degree of PTFE surface modification. Treatment time: 0.5 minutes to 120 minutes.

[0051] Plasma gas: preferably argon (Ar), oxygen (O2), nitrogen (N2) or ammonia (NH3). The gas flow rate is controlled at 10 to 50 sccm (standard cubic centimeters per minute).

[0052] The plasma treatment device is evacuated to a low pressure state of 10 to 100 Pa, the plasma generator is started, the gas introduction rate is controlled at 10 to 30 sccm, and the treatment is continued.

[0053] Step 3: Wash the plasma-treated polytetrafluoroethylene powder, and then dry it to obtain highly dispersed polytetrafluoroethylene powder.

[0054] Place the plasma-treated PTFE powder in a beaker and add an appropriate amount of solvent (such as ethanol or water) to wash it to remove the PEGDME that is not grafted on the surface. Use a magnetic stirrer to stir at 300 rpm for 30 minutes, then let it stand, filter the supernatant, and repeat the washing 2 to 3 times to ensure that all unbound PEGDME is removed.

[0055] The washed PTFE powder is used to absorb the residual solvent on the surface with filter paper, and then placed in a drying oven for drying at a temperature of 50°C to 80°C for 1 to 2 hours. After drying, samples are taken to observe the morphology of the PTFE powder to ensure that the particles are uniform and without obvious agglomeration.

[0056] The contact angle of the PTFE powder before and after modification was measured using a contact angle tester to evaluate the change in surface wettability. The change in the dispersion of PTFE in the dry electrode powder was evaluated using a scanning electron microscope.

[0057] The present invention adopts surface modification technology, such as surfactant treatment, plasma treatment or chemical introduction of hydrophilic groups (hydroxyl, carboxyl, etc.), to reduce the hydrophobicity of the PTFE surface and improve its compatibility with other powders, thereby improving the dispersion effect. The particle size, morphology and molecular weight of PTFE are controlled, its dispersion behavior is optimized, and particle agglomeration is avoided. The surface modification of PTFE improves its powder dispersibility, increases electrolyte wettability, and improves electrochemical performance.

[0058] The chemical reaction principle of the present invention is:

[0059] 1. PTFE surface activation: The original PTFE chain is treated with plasma to form a PTFE chain of carbon free radicals, and the reaction formula is:

[0060] ...–CF2–CF2–CF2–CF2–…

[0061] |

[0062] Plasma treatment

[0063] ↓

[0064] ...–CF2–C•F–CF2–C•F–… .

[0065] 2. Activation of PEGDME: The original PEGDME chain is treated with plasma to form a carbon radical PEGDME chain, and the reaction formula is:

[0066] CH3O–[CH2–CH2–O] n –CH3

[0067] |

[0068] Plasma treatment

[0069] ↓

[0070] CH3O–[CH2–C•H–O] n –CH3.

[0071] 3. Free radical coupling: The carbon radical PTFE chain and the carbon radical PEGDME chain are coupled to form the grafted PTFE-PEGDME chain:

[0072] Activated PTFE chain + activated PEGDME chain

[0073] |

[0074] Combination

[0075] ↓

[0076] ...–CF2–CF(–CH2–[O–CH2–CH2] n –O–CH3)–CF2–… .

[0077] Comparative Example 1

[0078] Select 10g of PTFE powder with a particle size of 5 microns, mix it evenly with 100mL of aqueous solution, and stir it magnetically at room temperature of 25℃ for 2 hours. After stirring, put the PTFE powder into a drying oven and dry it at 60℃ for 2 hours to ensure that the water is completely volatilized. The dried PTFE powder is evenly spread on the sample tray of the plasma treatment device, a plasma generator with a power of 100W is selected, and an argon flow rate of 10sccm is introduced. It is treated for 30 minutes at a vacuum degree of 50 Pa. After the plasma treatment, the normal pressure is slowly restored, and the modified PTFE powder is taken out and washed with deionized water 3 times, each time for 10 minutes. The stirring speed during the washing process is set to 300 rpm, and then the washed PTFE powder is placed in a drying oven and dried at 60℃ for 1 hour. PTFE is used as a binder to prepare dry electrode plates, and the resistivity of each position of the plate is measured by the four-probe method. The statistical results are shown in Table 1. Please refer to each position Figure 2 . Example 1

[0079] Select 10g of PTFE powder with a particle size of 5 microns, mix it evenly with 100mL of PEGDME-400 aqueous solution with a concentration of 10%, and stir it magnetically for 2 hours at room temperature of 25℃ to ensure that PEGDME is evenly distributed on the surface of PTFE powder. After stirring, put the coated PTFE powder into a drying oven and dry it at 60℃ for 2 hours to ensure that the solvent is completely volatilized. The dried PTFE powder is evenly spread on the sample tray of the plasma treatment device, a plasma generator with a power of 100W is selected, and a 10sccm argon flow rate is introduced, and the treatment is carried out for 30 minutes under a vacuum degree of 50 Pa. After the plasma treatment, the normal pressure is slowly restored, and the modified PTFE powder is taken out and washed with deionized water 3 times, each time for 10 minutes. The stirring speed during the washing process is set to 300 rpm to ensure that the ungrafted PEGDME is completely removed. Then the washed PTFE powder is placed in a drying oven and dried at 60℃ for 1 hour. The modified PTFE was used as a binder to prepare dry electrode plates. The resistivity of each position of the plates was measured by the four-probe method. The statistical results are shown in Table 1. Example 2

[0080] Select 10g of PTFE powder with a particle size of 10 microns, mix it evenly with 100mL of PEGDME-5000 aqueous solution with a concentration of 20%, and stir it magnetically for 2 hours at room temperature of 25℃ to ensure that PEGDME is evenly distributed on the surface of PTFE powder. After stirring, put the coated PTFE powder into a drying oven and dry it at 60℃ for 2 hours to ensure that the solvent is completely volatilized. The dried PTFE powder is evenly spread on the sample tray of the plasma treatment device, a plasma generator with a power of 100W is selected, and a 10sccm argon flow rate is introduced, and the treatment is carried out for 30 minutes under a vacuum degree of 50 Pa. After the plasma treatment, the normal pressure is slowly restored, and the modified PTFE powder is taken out and washed with deionized water 3 times, each time for 10 minutes. The stirring speed during the washing process is set to 300 rpm to ensure that the ungrafted PEGDME is completely removed. Then the washed PTFE powder is placed in a drying oven and dried at 60℃ for 1 hour. The modified PTFE was used as a binder to prepare dry electrode plates. The resistivity of each position of the plates was measured by the four-probe method. The statistical results are shown in Table 1. Example 3

[0081] Select 10g of PTFE powder with a particle size of 20 microns, mix it evenly with 100mL of PEGDME-20000 aqueous solution with a concentration of 30%, and stir it magnetically for 2 hours at room temperature of 25℃ to ensure that PEGDME is evenly distributed on the surface of PTFE powder. After stirring, put the coated PTFE powder into a drying oven and dry it at 60℃ for 2 hours to ensure that the solvent is completely volatilized. The dried PTFE powder is evenly spread on the sample tray of the plasma treatment device, a plasma generator with a power of 100W is selected, and a 10sccm argon flow rate is introduced, and the treatment is carried out for 30 minutes under a vacuum degree of 50 Pa. After the plasma treatment, the normal pressure is slowly restored, and the modified PTFE powder is taken out and washed with deionized water 3 times, each time for 10 minutes. The stirring speed during the washing process is set to 300 rpm to ensure that the ungrafted PEGDME is completely removed. Then the washed PTFE powder is placed in a drying oven and dried at 60℃ for 1 hour. The modified PTFE was used as a binder to prepare dry electrode plates. The resistivity of each position of the plates was measured by the four-probe method. The statistical results are shown in Table 1. Example 4

[0082] Select 10g of PTFE powder with a particle size of 25 microns, mix it evenly with 100mL of PEGDME-50000 aqueous solution with a concentration of 25%, and stir it magnetically for 2 hours at room temperature of 25℃ to ensure that PEGDME is evenly distributed on the surface of PTFE powder. After stirring, put the coated PTFE powder into a drying oven and dry it at 60℃ for 2 hours to ensure that the solvent is completely volatilized. The dried PTFE powder is evenly spread on the sample tray of the plasma treatment device, a plasma generator with a power of 100W is selected, and a 10sccm argon flow rate is introduced, and the treatment is carried out for 30 minutes under a vacuum degree of 50 Pa. After the plasma treatment, the normal pressure is slowly restored, and the modified PTFE powder is taken out and washed with deionized water 3 times, each time for 10 minutes. The stirring speed during the washing process is set to 300 rpm to ensure that the ungrafted PEGDME is completely removed. Then the washed PTFE powder is placed in a drying oven and dried at 60℃ for 1 hour. The modified PTFE was used as a binder to prepare dry electrode plates. The resistivity of each position of the plates was measured by the four-probe method. The statistical results are shown in Table 1.

[0083]

[0084] The dry electrode plate of the embodiment of the present invention includes a highly dispersible polytetrafluoroethylene powder prepared by the method for preparing highly dispersible polytetrafluoroethylene powder as described above. The highly dispersible polytetrafluoroethylene powder of the present invention is used as a dry electrode binder, and is uniformly fiberized with positive and negative electrode active materials, conductive agents, etc. under the action of high-speed shearing to prepare dry electrode powder, and then a dry electrode plate is prepared from the dry electrode powder.

[0085] The present invention can use a four-probe method to characterize the dispersion uniformity of PTFE in a dry electrode plate.

[0086] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing highly dispersible polytetrafluoroethylene powder, characterized in that: include: Step 1: impregnating polytetrafluoroethylene powder with a polyethylene glycol dimethyl ether solution, taking out the polytetrafluoroethylene powder after the impregnation, removing the residue on the surface of the polytetrafluoroethylene powder and drying to obtain a coated polytetrafluoroethylene powder; the molecular weight of the polyethylene glycol dimethyl ether is 400-100000; Step 2: Plasma-treating the coated polytetrafluoroethylene powder to obtain plasma-treated polytetrafluoroethylene powder; Step 3: Wash the plasma-treated polytetrafluoroethylene powder, and then dry it to obtain highly dispersed polytetrafluoroethylene powder.

2. The method for preparing highly dispersible polytetrafluoroethylene powder according to claim 1, characterized in that: The particle size of the polytetrafluoroethylene powder impregnated with the polyethylene glycol dimethyl ether solution is 1 to 20 microns.

3. The method for preparing highly dispersible polytetrafluoroethylene powder according to claim 1, characterized in that: The polyethylene glycol dimethyl ether solution is a polyethylene glycol dimethyl ether solution containing a solvent or a polyethylene glycol dimethyl ether solution without a solvent.

4. The method for preparing highly dispersible polytetrafluoroethylene powder according to claim 3, characterized in that: The concentration range of the polyethylene glycol dimethyl ether solution is 5% to 100%.

5. The method for preparing highly dispersible polytetrafluoroethylene powder according to claim 1, characterized in that: In step 1, the immersion temperature is 20°C to 150°C, the immersion time is 1 to 24 hours, and the drying temperature is 10°C to 150°C.

6. The method for preparing highly dispersible polytetrafluoroethylene powder according to claim 5, characterized in that: During the impregnation process, ultrasonic treatment was used to accelerate the penetration of the polyethylene glycol dimethyl ether solution into the surface of the polytetrafluoroethylene particles.

7. The method for preparing highly dispersible polytetrafluoroethylene powder according to claim 1, characterized in that: In step 2, the plasma treatment time is 0.5 minutes to 120 minutes.

8. The method for preparing highly dispersible polytetrafluoroethylene powder according to claim 1, characterized in that: In step 2, the plasma gas for plasma treatment is one or more of argon, oxygen, nitrogen and ammonia, and the plasma gas flow rate is 10 to 50 sccm.

9. The method for preparing highly dispersible polytetrafluoroethylene powder according to claim 1, characterized in that: The drying temperature is 50°C to 80°C, and the drying time is 1 to 2 hours.

10. A dry electrode plate, characterized in that: The invention comprises a highly dispersible polytetrafluoroethylene powder prepared by the method for preparing a highly dispersible polytetrafluoroethylene powder as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Surface modification method for polytetrafluoroethylene product

    CN101979429A

  • Modified binder and preparation method thereof, dry-method electrode plate and battery

    CN117691110A